Western Association of Vertebrate Paleontology Abstracts, 2019 Meeting (Bulletin of the Museum of Natural History, University of Oregon, 2019)
Abstracts from the 2019 meeting of the Western Association of Vertebrate Paleontology meeting, held in Eugene OR, on March 15-17.